2019
DOI: 10.1002/jia2.25324
|View full text |Cite
|
Sign up to set email alerts
|

Switch to dolutegravir is well tolerated in Thais with HIV infection

Abstract: Introduction Dolutegravir (DTG) is recommended as part of first‐line antiretroviral therapy (ART) for people living with HIV(PLHIV). We sought to determine the rate of adverse events (AEs) and discontinuations among Thais treated during acute HIV infection (AHI) and switched to DTG‐based regimens. Methods Thai participants in the SEARCH010/RV254 cohort who initiated ART during AHI and switched to DTG for at least 48 weeks were prospectively observed and included in the analysis. Rates and characteristics of DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In any case, all women of childbearing age were subsequently informed of the need to use effective contraceptive methods while continuing treatment. Finally, the weight gain reported with the use of DTG in clinical trials and some cohorts 29-31 could not be analyzed in detail in this study because of the lack of consistency in the registration of patients’ weight in the clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, all women of childbearing age were subsequently informed of the need to use effective contraceptive methods while continuing treatment. Finally, the weight gain reported with the use of DTG in clinical trials and some cohorts 29-31 could not be analyzed in detail in this study because of the lack of consistency in the registration of patients’ weight in the clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…The Netherlands. 5 Memory and Aging Center, Department of Neurology, University of California San Francisco, San Francisco, CA, USA. 6 Center for Neuroepidemiology and Clinical Neurological Research, Yale University, New Haven, CT, USA.…”
Section: Additional Informationmentioning
confidence: 99%
“…Additionally, neurocognitive performance before and after DTG-based ART is not well defined [2]. We previously reported that DTG was well tolerated with few discontinuations among young men who switched from a non-DTG to a DTG-based regimen [5]. This follow-up report focuses on affective and somatic dimensions of depression, and cognitive performance before and after switch to DTG.…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Africa, dolutegravir (DTG), an integrase inhibitor drug, is being introduced on a large scale as part of fixed-dose combinations of Tenofovir, Lamivudine, and Dolutegravir (TLD) [5]. With a high genetic barrier to resistance, DTG has the potential to curb the spread of antiretroviral resistance, as it is highly effective, well tolerated, and affordable in resourcelimited settings [6][7][8][9]. Mathematical models explored the effectiveness and cost-effectiveness of prescribing DTG to all ART initiators [10].…”
Section: Introductionmentioning
confidence: 99%